Countries three wise men: Sustainability, innovation, and competitiveness - Luis Miguel Ciravegna Martins da Fonseca; Vanda Marlene Lima (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The studies on links between sustainability, innovation, and competitiveness have been mainly focused at organizational and business level. The purpose of this research is to investigate if there is a correlation between these three variables at country level. Using international well recognized rankings of countries sustainability, innovation, and competitiveness, correlation analysis was performed allowing for the conclusion that there are indeed high correlations (and possible relationships) between the three variables at country level. Design/methodology/approach: Sustainability, innovation, and competitiveness literature were reviewed identifying a lack of studies examining these three variables at country level. Three major well recognized indexes were used to support the quantitative research: The World Economic Forum (2013) Sustainability-adjusted global competitiveness index, the Global Innovation Index (2014) issued by Cornell University, INSEAD, and WIPO and the IMD World Competitiveness Yearbook (2014). After confirming the distributions normality, Pearson correlation analysis was made with results showing high linear correlations between the three indexes. Findings: The results of the correlation analysis using Pearson correlation coefficient (all correlation coefficients are greater than 0.73) give a strong support to the conclusion that there is indeed a high correlation (and a possible relationship) between social sustainability, innovation and competitiveness at country level. Research limitations/implications: Further research is advisable to better understand the factors that contribute to the presented results and to establish a global paradigm linking these three main constructs (social sustainability, innovation, and competitiveness). Some authors consider that these measurements are not fully supported (e.g. due to different countries standards), however, it is assumed these differing underlying methodological approaches, by being used in conjunction, can be considered as a set of reliable and useful performance indicators. Practical implications: The results highlight the simultaneous relationship between social sustainability, innovation and competitiveness superior performance and the need to take that these considerations into business and operating models. Social implications: This research suggests that sustainability and innovation policies, strategies and practices are relevant for countries competitiveness and should be promoted particularly in countries ranked low on sustainability and innovation global scoring indexes. Originality/value: This is one of the few studies addressing the relationships between sustainability, innovation and competitiveness at country level.
Keywords: 650; sustainability; corporate social responsibility; innovation; countries competitiveness